2018
DOI: 10.3390/molecules23030683
|View full text |Cite
|
Sign up to set email alerts
|

Hyperjaponol H, A New Bioactive Filicinic Acid-Based Meroterpenoid from Hypericum japonicum Thunb. ex Murray

Abstract: Hyperjaponol H (1), a new filicinic acid-based meroterpenoid, with a 6/6/10 ring system trans-fused by hetero-Diels–Alder cycloaddition between a germacrane sesquiterpenoid and a filicinic acid moiety, was isolated from aerial parts of Hypericum japonicum. The elucidation of its structure and absolute configuration were accomplished by the analyses of extensive spectroscopic data and the comparison of Cotton effects of electron circular dichroism (ECD) with previously reported ones. The bioactivity assay showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Hyperjaponol H (143) is a hybrid of tasmanone and the monoterpene germacrane. An assay on lytic DNA replication of EBV in B95-8 cells indicated that this compound displayed moderate inhibitory effects with an EC 50 value of 25.00 µM [60] (Table 2). Spectroscopic identification of the secondary metabolites of Rhodomyrtus tomentosa revealed that tomentosenol A (144), 4S-focifolidione (145) and 4R-focifolidione (146) contain a unique free syncarpic acid-derived meroterpenoid skeleton.…”
Section: Syncarpic Acid/β-triketones-based Meroterpenesmentioning
confidence: 99%
“…Hyperjaponol H (143) is a hybrid of tasmanone and the monoterpene germacrane. An assay on lytic DNA replication of EBV in B95-8 cells indicated that this compound displayed moderate inhibitory effects with an EC 50 value of 25.00 µM [60] (Table 2). Spectroscopic identification of the secondary metabolites of Rhodomyrtus tomentosa revealed that tomentosenol A (144), 4S-focifolidione (145) and 4R-focifolidione (146) contain a unique free syncarpic acid-derived meroterpenoid skeleton.…”
Section: Syncarpic Acid/β-triketones-based Meroterpenesmentioning
confidence: 99%
“…ex Murray, also known as Di-er-cao or Tian-ji-huang, which has been used in jaundice treatment since the Qing dynasty. H. japonicum has the functions of clearing heat, removing dampness, calming the liver, and enhancing the gallbladder and is commonly used in the clinical treatment of damp-heat jaundice [ 10 ]. The chemical composition of H. japonicum includes flavonoids, xanthonoids, chromone glycosides, phloroglucinol derivatives, and lactones.…”
Section: Introductionmentioning
confidence: 99%
“…Natural products are extensively known to be a major resource of biologically active compounds that hold manifold and unusual platforms [1]. Terpenoids are structurally differing secondary metabolites with more than 40,000 reported structural diversity bearing valuable bioactive characters [2,3] Their structures are chiefly sourced from plants and microbes, which are mainly biosynthesized by the 2-C-methylerythritol 4-phosphate pathway or the mevalonate pathway [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Terretonintype ( Figure 10) congeners bearing a δ-lactone in ring D are derived from terrenoid (andrastin-type) by D-ring expansion and bizarre rearrangement of the methoxy group [78]. Berkeleyone-type (or protoaustinoid-type) ( Figure 11) derivatives being the caspase-1 inhibitor is the meroterpenoids defining a set of unique and functionalized chemical scaffolds, which are identified by the existence bicyclo [3.3,1]nonane or its rearranged bicyclo [3,2,1]octane unit in rings C and D [79], and are originated by the same intermediate as for andrastins with miscellaneous rearrangement. Austinol ( Figure 12) and its analogs displayed a pentacyclic scaffold with a spiro-δlactone in ring A and a γ-lactone in ring E, that was originated from protoaustinoid through oxidation and ring rearrangement [80].…”
Section: Introductionmentioning
confidence: 99%